Ekonomi, Hukum dan Lingkungan Dalam Undang-Undang Cipta Kerja - Abdul Rahman (Lex Renaissance, 2022)
This study aims to identify and analyze the legal conception as a means of development as well as to analyze the nature of the relationship between the economy, law and the environment contained in the Job Creation Law. This study uses normative legal research with a statutory and conceptual approach. The results of the study conclude, first, that development efforts carried out by the government should focus on the doctrine of sustainable development which is supported by an understanding of development law which will later become the government's insight in realizing sustainable economic growth. Second, the Job Creation Law, which is expected to be able to answer the problems of the times, does not work as desired because the development approach used prioritizes economic interests without paying attention to the environmental impact of economic activities.. Key Words: Economics; law; environment; sustainable development AbstrakPenelitian ini bertujuan untuk mengidentifikasi dan menganalisa konsepsi hukum sebagai sarana pembangunan serta menganalisis corak hubungan antara ekonomi, hukum dan lingkungan yang ada dalam Undang-Undang Cipta Kerja. Penelitian ini menggunakan penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Hasil dari penelitian menyimpulkan, pertama, upaya pembangunan yang dilakukan oleh pemerintah sudah seharusnya menitik beratkan pada doktrin pembangunan berkelanjutan yang di topang oleh paham hukum pembangunan yang nantinya akan menjadi wawaasan pemerintah dalam mewujutkan pertumbuhan ekonomi yang berkelanjutan. Kedua, Undang-Undang cipta kerja yang diharapkan mampu menjawab permasalahan zaman tak berjalan sesuai keinginan dikarenakan pendekatan pembangunan yang digunakan lebih mengedepankan kepentingan ekonomi tanpa memperhatikan dampak lingkungan dari kegiatan perekonomian. Kata-kata Kunci: Ekonomi; hukum; lingkungan; pembangunan berkelanjutan